Professional Ethics as an Important Part of Engineer Training in Technical Higher Education Institutions - Lapuzina, O.; Romanov, Yu.; Lisachuk, Lidiya (Wydawnictwo Adam Marszałek, 2018)
This article underscores the importance of professional ethics studies for future engineers in a modern education system. The purpose of the research was to show how university teachers could help future engineers acquire their skills in techno ethics, ecological ethics, computer ethics skills, etc., by teaching an interactive course "Professional Ethics for Engineers". The research was conducted using data obtained from 418 university students and 88 engineers. The results of the completion of the course made it possible to conclude that the case study method would become an effective tool to form future engineers’ professional needs, interests, opinions, life values, and positive world outlook.
Keywords: professional ethics; techno ethics; ecological ethics; computer ethics; modern engineer training; higher technical education